(The relationship between electronic accounting information systems and the degree of bank credit risk (Field study on specialized Sudanese banks - Taha, Mohamed ElMoataz ElMojtaba Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2017)
The study examined the role of accounting information systems to reduce the risk of electronic credit bank. The problem with the study is that the banks are exposed to the failures , in the event of failed management in the recruitment of accounting information systems , electronic tapped to serve and support its own operations in making investment decisions in general, and the decisions of the granting of credit in the banks , in particular the most part due failures in the field of credit to the problems in the measurement of risk credit , which represents state banks face at the present time which makes it tough in the granting of credit . This study is important from the importance of accounting information systems electronic as a strategy has become a strategic resource dependent upon the banks to deal with the market conditions when making decisions to grant credit, as banks must stand on the degree of credit risk for credit operations that have been granted to customers, so before making a decision to grant loans new in order to stand on the truth and put . The study aimed to identify the characteristics of the electronic accounting information systems in terms of speed in providing information and in terms of the accuracy of information and reflection on the measurement of credit risk in banks, the formulation of the theoretical aspects of the accounting information systems and electronic use them to improve the process of measuring credit risk. The study relied on deductive approach and inductive and historical approach descriptive and concluded several results, most important , study results indicated accounting information systems electronic affect the credit risk of the bank, confirmed the findings of the study and a relationship with a significance between rehabilitation personnel information systems, accounting and reduce the credit risk of the bank, results indicated study indicated that the accounting information systems electronic increase the credibility of accounting information . The study recommended a number of recommendations, including the need to make sure the loan guarantee granted by the credit risk faced by the bank through electronic accounting information system, focusing on the importance of the information system of accounting -mail addresses for being immediate loans when due.